Effects of economic structural transition on PM2.5-Related Human Health Impacts in China. (20th May 2021) - Wu, Xiaohui; Yang, Xuechun; Qi, Jianchuan; Feng, Cuiyang; Liang, Sai
Abstract: China has been experiencing significant economic structural transition and PM2.5 -Related Human Health Impacts (PM2.5 -HHI). However, the effects of economic structural transition on PM2.5 -HHI in China remain unclear. Our study analyzes the relative contributions of the changes in economic structural factors (including production structure, final demand structure, and emission source structure) to changes in China's PM2.5 -HHI during 1990–2015, using the input-output based structural decomposition analysis. Results show that the change in production structure generally has contributed to reducing PM2.5 -HHI since 2009. The change in final demand structure leads to an increase in PM2.5 -HHI. Moreover, the driving effect of fixed capital formation on the increase in PM2.5 -HHI is significantly enhanced. The change in emission source structure has contributed to reducing PM2.5 -HHI since 1995, mainly due to the optimization of energy use structures. Our findings can provide scientific supports for economic structural regulations to reduce PM2.5 -HHI in China. Besides strengthening the end-of-pipe PM2.5 emission control of key sectors, special attention should be paid to the structural factors optimization that have great potentials of reducing PM2.5 -HHI. Highlights: Production and emission source structure changes reduced recent health impacts. Final demand structure change led to health impact increments. Optimizing economic structural factors help control health impacts.